2015
DOI: 10.1039/c5ta02860d
|View full text |Cite
|
Sign up to set email alerts
|

One-step encapsulation of Pd nanoparticles in MOFs via a temperature control program

Abstract: A facile cooperative in situ metal precursor incorporation and on-site moderate reduction strategy is established for one step encapsulation of Pd nanoparticles in the pore of MOFs, which could not be achieved by a quick heating process.The control over size and location of metal nanoparticles (MNPs) within metal-organic frameworks (MOFs) is achieved in one step through a cooperative in situ incorporation of metal precursor and on-site moderate reduction process, which is operated by temperature programming co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…The obtained products were characteristic of Pd NPs of 3.2 nm in diameter homogeneously distributed inside UiO‐67(Zr) and its loading of 1 mol%. Also, Li et al reported a simple temperature control program to encapsulate Pd NPs inside UiO‐67(Zr) with its loading of 1.0 wt% . This process involved incorporation of PdCl 2 (CH 3 CN) 2 into the mixture of ZrCl 4 , 2,2′‐bipyridine‐5,5′‐dicarboxylate, DMF and HCl at 80 °C and on‐site moderate reduction process to fabricate Pd NPs at an elevated temperature of 130 °C.…”
Section: Controllable Synthesis Of Active Nps Encapsulated By Mofsmentioning
confidence: 99%
“…The obtained products were characteristic of Pd NPs of 3.2 nm in diameter homogeneously distributed inside UiO‐67(Zr) and its loading of 1 mol%. Also, Li et al reported a simple temperature control program to encapsulate Pd NPs inside UiO‐67(Zr) with its loading of 1.0 wt% . This process involved incorporation of PdCl 2 (CH 3 CN) 2 into the mixture of ZrCl 4 , 2,2′‐bipyridine‐5,5′‐dicarboxylate, DMF and HCl at 80 °C and on‐site moderate reduction process to fabricate Pd NPs at an elevated temperature of 130 °C.…”
Section: Controllable Synthesis Of Active Nps Encapsulated By Mofsmentioning
confidence: 99%
“…In contrast, for the corresponding Pd/ZrO 2 @C derived from Pd@UiO‐66(Zr) under the same conditions, a sharp diffraction peak at around 40 °C ascribed to the Pd species was clearly observed (Figures S1 and S2 in the Supporting Information), suggesting that the Pd species significantly aggregated during the thermal transformation procedure. This comparison demonstrates that amine groups are indispensable for the dispersion of ultra‐small Pd nanoclusters . Further calculations using the Scherrer equation revealed that the size of the Pd nanoparticles in Pd/ZrO 2 @C was about 13 nm.…”
Section: Resultsmentioning
confidence: 97%
“…By further pyrolysis at high temperature under an inert atmosphere, the organic linkers and inorganic Zr‐based anodes of NH 2 ‐UiO‐66(Zr) were converted into nitrogen‐doped porous carbon and ZrO 2 nanoparticles, respectively. The ‐NH 2 groups in the formed MOFs are vital for the fabrication of ultra‐small Pd nanoclusters as these groups can largely impede the migration of Pd nanoclusters at high temperatures owing to the strong interaction between the lone‐pair electrons of the N species and the 5d empty orbitals of the Pd ions . In contrast, without the assistance of the ‐NH 2 groups, the Pd species were inclined to aggregate into relatively large nanoparticles upon pyrolysis of the counterpart Pd@UiO‐66(Zr).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a temperature‐controlled program has been successfully utilized in one‐step encapsulation of Pd NPs in MOFs (i.e., UiO‐67) 41. The synthesis route followed a cooperative in situ metal precursor incorporation (e.g., 80°C) and an on‐site moderate reduction process to fabricate MNPs at elevated temperatures (e.g., 130°C).…”
Section: Decoration Of Mofs: Postsynthetic Strategymentioning
confidence: 99%
“…b) Catalytic hydrogenation of styrene to ethylbenzene. c) Yield of ethylbenzene versus time in the hydrogenation of styrene over Pd II ‐in‐UiO‐67, Pd‐in‐UiO‐67, and Pd@UiO‐67 41…”
Section: Decoration Of Mofs: Postsynthetic Strategymentioning
confidence: 99%